In-Vitro and In-Vivo Study of Fluorouracil Loaded Solid Lipid Nanoparticle in The Treatment of Skin Cancer - Sharma, Bhavik; Bhargava, Amit (Journal of Neonatal Surgery, 2025)
The cancer medicine Fluorouracil functions as an antimetabolite for widespread clinical treatment of various cancers. A systemic administration of the drug causes strong adverse reactions which negatively affect its medical efficacy. A study of topical delivery methods emerged to solve the current problems in skin cancer treatments. The therapeutic benefits of this technique are limited because the drug struggles to penetrate through the skin barrier. The researchers developed Fluorouracil solid lipid nanoparticles into a gel formulation because it improves drug administration by skin along with enhanced therapeutic outcomes and reduced exposure levels in systemic and toxic areas. A research project concentrated on making Fluorouracil dermal penetration more effective through SLN formulation development for skin cancer treatment. The in vitro drug release evaluation incorporated zero order, first order, Higuchi and Korsmeyer-Peppas models to study the release profile but Korsmeyer-Peppas provided the optimal fit that confirmed drug release through a diffusion-controlled mechanism. Laboratory tests analysed acute Fluorouracil-loaded SLN gel toxicities by giving animals treatment amounts from 25 mg/kg to 70 mg/kg. The monitoring of treated animals revealed no mortality or physical abnormalities during a 15-day period. This evidence demonstrates the formulated product is secure for use.